Electrophysiologically distinct bed nucleus of the stria terminalis projections to the ventral tegmental area in mice - Miura, Yuka; Shanley, Mary Regis; Urbaez, Ashley; Friedman, Allyson K. (Frontiers in Neural Circuits, 2023)
The bed nucleus of the stria terminalis (BNST) is a highly heterogeneous limbic forebrain structure that serves as a relay connecting autonomic, neuroendocrine and behavioral functions. It can be divided into over 16 individual subregions with distinct neuronal subpopulations based on receptors, transmitters and neuropeptides. Specifically, the BNST projection to the ventral tegmental area (VTA), the dopamine hub of the brain, has been shown to have a crucial role in the stress response. However, in mice there is a lack of unbiased data on the functional diversity of this sub-population which serves as an upstream input to the VTA. The dopaminergic neurons in the VTA modify their ion channel activity and intrinsic membrane properties to adapt to stress in part from inputs from BNST projections. Therefore, we aimed to perform a multi-component characterization of the functional diversity of the BNST-VTA pathway. We studied the passive and active electrophysiological properties of virally identified population of BNST neurons that project to the VTA. We used a comprehensive series of in vitro recordings of electrophysiological variables and performed hierarchical clustering to determine the functional diversity of the projection neurons in the BNST-VTA pathway. Our study revealed four subpopulations in the BNST-VTA pathway, all of which differ in their activation profiles and likely have distinct inputs and function in the VTA. Our results will help resolve the discord in interpretation of the various roles of this electrophysiologically diverse projection and builds a foundation for understanding how the different neuronal types integrate signals.